2018
DOI: 10.1097/acm.0000000000002119
|View full text |Cite
|
Sign up to set email alerts
|

Charting the Publication and Citation Impact of the NIH Clinical and Translational Science Awards (CTSA) Program From 2006 Through 2016

Abstract: The CTSA program is yielding a robust and growing body of influential research findings with consistently high indices of relative citation impact. Preliminary evidence suggests multi-institutional collaborations and more monetary resources are associated with elevated bibliometric activity and, therefore, may be worth their investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…CTSA-wide citation influence has been reported in the past (Frechtling, Raue, Michie, Miyaoka, & Spiegelman, 2012; Leshner et al, 2013; Steketee et al, 2012) but not with respect to disciplinary area. Because current citation influence metrics are benchmarked against other publications from the same research areas (Hutchins, Yuan, Anderson, & Santangelo, 2016; Llewellyn et al, 2018; Reuters, 2014), it is important to understand the disciplinary context within which articles are compared. This study utilizes multiple article- and journal-level citation metrics to triangulate aggregate and field-specific citation influence, allowing for a nuanced consideration of influence within and across research areas.…”
Section: Relative Influence Of Research Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…CTSA-wide citation influence has been reported in the past (Frechtling, Raue, Michie, Miyaoka, & Spiegelman, 2012; Leshner et al, 2013; Steketee et al, 2012) but not with respect to disciplinary area. Because current citation influence metrics are benchmarked against other publications from the same research areas (Hutchins, Yuan, Anderson, & Santangelo, 2016; Llewellyn et al, 2018; Reuters, 2014), it is important to understand the disciplinary context within which articles are compared. This study utilizes multiple article- and journal-level citation metrics to triangulate aggregate and field-specific citation influence, allowing for a nuanced consideration of influence within and across research areas.…”
Section: Relative Influence Of Research Areasmentioning
confidence: 99%
“…Thus far, descriptions of the CTSA consortium’s overall publication and citation activity over the first 5 and 10 years of the program have been reported (Llewellyn, Carter, Rollins, & Nehl, 2018; Steketee, Frechtling, Cross, & Schnell, 2012). These studies showed that the quantity of publications supported by CTSA hubs is robust and accelerating over time and that their citation influence is consistently well above global averages for their fields and years of publication.…”
mentioning
confidence: 99%
“…This identification demonstrated that NC TraCS continues to support the mission of NCATS. The topic mapping metrics of NC TraCS-supported publications go beyond the scope of bibliometrics by measuring the foci of translational science activities at an institution [16,38].…”
Section: Discussionmentioning
confidence: 99%
“…It is a validated method to quantify the influence of a research article [31]. With a customizable benchmarking feature, RCRs can be used to compare research performance across different fields and research groups [16,30].…”
Section: Data Toolsmentioning
confidence: 99%
See 1 more Smart Citation